Institutional Inertia and Pedagogical Disruption: How Teachers Negotiate Curriculum Innovation Under Mandated Reform Conditions - Isabel López; Ricardo Sánchez; Patricia Ramírez (Journal of Loomingulisus ja Innovatsioon, 2026)
Curriculum reforms have become a central strategy for improving educational quality, yet their implementation frequently encounters institutional resistance and inconsistent classroom enactment. Existing research has predominantly examined curriculum change from policy or leadership perspectives, providing limited understanding of how teachers actively negotiate innovation within organizational environments characterized by institutional inertia. This study aimed to investigate the interactions among teacher agency, institutional inertia, instructional leadership, professional collaboration, and pedagogical adaptation during the implementation of mandated curriculum reform. A mixed-methods sequential explanatory research design was employed involving 540 secondary school teachers from thirty public schools implementing a nationally mandated curriculum. Quantitative data were collected using standardized measures of teacher agency, organizational climate, leadership support, professional collaboration, instructional innovation, curriculum implementation, and professional self-efficacy, complemented by school documentation and classroom supervision records. Qualitative evidence was obtained through semi-structured interviews, focus group discussions, classroom observations, reflective teaching journals, leadership interviews, and policy document analysis. Findings revealed that teacher agency, instructional leadership, and collaborative professional learning significantly strengthened pedagogical innovation, whereas institutional inertia exerted a negative but manageable influence through supportive organizational conditions. Teachers consistently interpreted curriculum reform as an adaptive professional process rather than a procedural policy obligation. Results suggest that sustainable curriculum innovation depends on dynamic interaction among organizational culture, professional autonomy, collaborative learning, and instructional leadership, providing an integrated framework for strengthening educational reform implementation across diverse institutional contexts.